(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article examines the key features of modernism in the works of T. S. Eliot, one of the leading poets and theorists of 20th-century English literature. It analyzes the artistic and philosophical characteristics of his poetry, including fragmentary composition, intertextuality, mythological method, the problem of personal alienation, and the crisis of spiritual values. Using examples from works such as "The Love Song of J. Alfred Prufrock," "The Waste Land," and "Four Quartets," the specifics of Eliot’s modernist worldview and his contribution to the development of world literature are revealed.